1999
DOI: 10.1002/(sici)1099-1573(199905)13:3<245::aid-ptr424>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral properties of a crude extract from a green alga Caulerpa taxifolia (Vahl) C. Agardh

Abstract: A crude extract of Caulerpa taxifolia was tested for its antiviral activity. The chloroform–methanol residue showed an interesting inhibitor effect in vitro toward the feline immunodeficiency virus (FIV), a valid model for studying the acquired immunodeficiency syndrome. This extract reduced the virus‐induced syncytia in the cultured cells, the viral reverse transcriptase activity and the viral capsid protein P24 expression. Copyright © 1999 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…This assay, based on the interaction between fusigenic FIV-infected cells, has been used with other natural products (Calderone et al, 1998;Nicoletti et al, 1999). After an incubation of six days all extracts showed an antiviral activity, with a pattern similar to that of destrane (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assay, based on the interaction between fusigenic FIV-infected cells, has been used with other natural products (Calderone et al, 1998;Nicoletti et al, 1999). After an incubation of six days all extracts showed an antiviral activity, with a pattern similar to that of destrane (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of natural products that have antiviral activity, previous studies have shown that inhibition of syncytium formation in CrFK cells is a useful screening method for de- tecting substances that block FIV infection, such as natural extracts (Nicoletti et al, 1999;Schmitt et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of the present study was to determine the potential of Caulerpa species as a natural remedy for gout. It was presented in the previous reports that CYN, the main secondary metabolite of Caulerpa species, has some unique properties such as anticarcinogenic, antiproliferative, apoptotic and antiviral effects [16][17][18][19]. Moreover, the enzyme inhibitory effects of CYN towards some medically important enzymes like phospholipase A 2 , lipase, lipoxygenase and amylase have been shown by some researchers [21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…CYN is the main secondary metabolite of Caulerpa species which was firstly isolated from Caulerpa prolifera [15]. So far, anticarcinogenic, antiviral and apoptotic properties of CYN have been reported [16][17][18][19][20]. These remarkable results motivated researchers to investigate the other properties of this metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the CYN isolated from the C. prolifera was firstly identified by Amico et al (1978). The importance of the CYN in biochemical and pharmacological research areas has been evaluated in several published papers (Mayer et al, 1993;Fischel et al, 1995;Bitou et al, 1999;Nicoletti et al, 1999;Barbier et al, 2001;Cavas et al, 2006;Cavas & Pohnert, 2010). There are a few numbers of published papers in the literature where caulerpenyne levels were compared among Caulerpa spp (Paul & Fenical, 1986;Meyer&Paul, 1992;Gavagnin et al, 1994;Amade&Lemée, 1998;Jung et al, 2002;Box et al, 2010a,b).…”
Section: Introductionmentioning
confidence: 99%